ANALYSIS OF BUDGET ADJUSTMENT DUE TO COVID-19 PANDEMIC - Alkam, Rahayu; Bangsawan, Achdian Anggreny (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2024)
This study emphasizes government reaction on budgeting during a crisis which is valuable for improving government”™s agility to deal with the same or unprecedented crisis in the future. This study aims to analyze budget adjustment as responses to COVID-19 pandemic at Makassar Local Government. This study used a qualitative approach. The data gathered from budget documents and other related documents as well as in-depth interviews. The results showed that the budget adjustments process was carried out through the implementation of regulations issued by the central government. However, its implementation has not been fully successful because there are still some provisions that have not been complied. (4) Conclusion and Suggestion. There are still weaknesses in the budget adjustment process and negative impacts from budget adjustment on the overall budget system. Future research is expected to explore deeper and in a broader context related to the constraints of the existing budget adjustment system, Unexpected Expenditure, and anticipatory budgeting by involving stakeholders other than budget makers.